المنهج الدراسي ٢٠١٣ لترقية نتيجة تعلم اللغة العربية - Dimyati, Afifuddin; Suparto; Zuhriyah, Latifatuz; Hikmiyah, Tadarrosatul (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
This study aims to determine the results of learning Arabic after using the 2013 syllabus in class X and to find out what problems occur when the 2013 syllabus is applied in teaching Arabic. The type of research used is quantitative method, which is a systematic scientific research method on the parts and phenomena and the causality of their relationships.  The purpose of quantitative research is to develop and use mathematical models, theories and/or hypotheses related to natural phenomena.  The subjects in this study were all teachers and students who were involved in Arabic subjects.  Samples were taken randomly, namely taking 52 students from class X. The data and research sources taken were divided into two parts, namely qualitative data and quantitative data. The results of the research include general views about schools and Arabic language teaching by using data sources in the form of library theory taken from documents and books that are compatible with scientific research as well as field sources carried out directly in the field by researchers.  In addition, interviews and documentation methods are also used